Urban images of Lima: the construction of the concept of “neighborhood”, it’s significance and the resignifications on the memory of its people - Cristóbal, Irene (2019)
The present text has for object to delineate practices and discourses around the category of “neighborhood”, through the narratives of actors and actresses, with regard to the place they live in, that is, precisely, the urbanization of El Retablo, placed in the district of Comas. As to the dimension of the practices, the questions that arise are the following: ¿which are the limits of my neighborhood? ¿What is its physiognomy? ¿Who circulates around it? And ¿how have they been produced? As far as the dimension of the discourses, the posed questions are the following: ¿what image of my neighborhood has been constructed? ¿How would this image look like? ¿What implications does belonging to my neighborhood has? ¿Who belongs in it? ¿What kind of roll does nostalgia has? Subsequently, the phenomenological perspective is the pertinent way to get to the direct experience of the actors, manifested in said narratives. One of the important findings is the idea to have multiple neighborhoods, along with the idea of having, too, multiple identities. It’s interesting to point out that said idea associates with the living time of a person, expressed on the years of residency in the place; but, most of all, with the remembered and idealized time, edited and represented on relevant images of a great symbolic weight for the people. That is to say, with signified time. For this reason, one could have multiple neighborhoods if one lived and grew up in diverse places before becoming an adult.On the contrary, the time of having resided wouldn’t generate greater identity if they had not been able to establish bonds or experiences that generate meaning.